COVID-19, mental health and its relationship with workplace accidents - Villalobos Álvarez, Diego Leonardo (2022)
The general objective of this article is to show the relationship that exists in the COVID-19 pandemic, the mental health of people and the propensity for work-related accidents in companies. Various results are shown that detail how COVID-19 has generated and is generating mental alterations in people such as post-traumatic stress disorder, PTSD for its acronym in English. Likewise, data are presented that report the influence of mental health as a precursor to workplace accidents in different industries, with which it can be concluded that COVID-19 needs a comprehensive approach in companies to prevent it from negatively impacting workers and they end up accident during their daily work. Some concrete actions are proposed to promote and avoid in companies so that workers can be better managed in times of a COVID-19 pandemic.